Honey Creek: Breakfast at the Honey Creek Cafe - Book 1 - Thomas, Jodi (New York : Zebra Books, 2021)
"Piper Jane Mackenzie, mayor of Honey Creek, won't let a major scandal rip her quirky hometown apart, or jeopardize her dream of one day running for higher office. So she's willing to welcome undercover detective Colby McBride, hired to help solve the mystery behind her wannabe fiancé's disappearance. Colby's cover? That he is an old boyfriend now begging Piper for a second chance - always when there are plenty of townsfolk around to witness his shenanigans. Piper hardly knows whether to laugh or cry, especially when she finds herself drawn to the handsome rascal. He's not the only newcomer she has to deal with. There's a new interim preacher in town, Sam Cassidy. Drifting from one assignment to another since his one love died, Sam isn't sure he's the right fit for Honey Creek. But as Piper knows, this is a place chock-full of surprises. And if she can keep her town - and her heart - from going completely off the rails, there may be a sweet, unexpected future in store ..."--Back cover.
Keywords: Man-woman relationships -- Fiction; Texas -- Fiction; Romance fiction